2000
DOI: 10.1056/nejm200012073432302
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon Alfa-2a in Patients with Chronic Hepatitis C and Cirrhosis

Abstract: In patients with chronic hepatitis C and cirrhosis or bridging fibrosis, 180 microg of peginterferon alfa-2a administered once weekly is significantly more effective than 3 million units of standard interferon alfa-2a administered three times weekly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
497
1
19

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 800 publications
(542 citation statements)
references
References 17 publications
24
497
1
19
Order By: Relevance
“…The development of pegylated IFNs with improved pharmacokinetics has been shown to yield a better efficacy and convenience than the conventional IFNs in the treatment of chronic hepatitis C. [41][42][43][44][45] Regarding the treatment of chronic hepatitis B, recent pilot trials also demonstrated that pegylated IFN was more effective than conventional IFN or other nucleotide/nucleoside analogues in either HBeAg-positive or -negative chronic hepatitis B. 8,10,15,25,45 Whether pegylated IFN-based therapy in combination with other antiviral agents such as ribavirin could enhance the treatment efficacy in patients with chronic hepatitis B awaits further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The development of pegylated IFNs with improved pharmacokinetics has been shown to yield a better efficacy and convenience than the conventional IFNs in the treatment of chronic hepatitis C. [41][42][43][44][45] Regarding the treatment of chronic hepatitis B, recent pilot trials also demonstrated that pegylated IFN was more effective than conventional IFN or other nucleotide/nucleoside analogues in either HBeAg-positive or -negative chronic hepatitis B. 8,10,15,25,45 Whether pegylated IFN-based therapy in combination with other antiviral agents such as ribavirin could enhance the treatment efficacy in patients with chronic hepatitis B awaits further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data on individual patients from three RCTs of peginterferon alfa-2a. 11,12,14 These studies are the only three RCTs that compare peginterferon alfa-2a with conventional IFN and include previously untreated patients with pretreatment and post-treatment liver biopsies. Written consent was obtained from the principal investigator at each trial center.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the results of published studies on the effects of this new drug on liver histology remain inconsistent, and the overall effect of treatment is difficult to evaluate. [11][12][13][14] To overcome some of the limitations associated with the use of histologic findings, to increase the relevance of statistical analysis, and to improve estimates of effect magnitudes, we performed a meta-analysis of individual patient data (MIPD). The aims of the current MIPD were 1) to assess the differences between peginterferon alfa-2a and conventional IFN with respect to changes in liver histology; 2) to identify predictors of histologic improvement; and 3) to evaluate the optimal treatment schedule for bringing about histologic improvement.…”
mentioning
confidence: 99%
“…Consequently, HCV infection is the foremost reason for performing liver transplants. 2 Antiviral therapy consisting of peginterferon alfa-2a/ribavirin leads to a sustained response in only half of all patients infected with HCV genotypes 1 and 4, 3,4 resulting in the need to develop new antiviral therapies. In addition, the emergence of drug resistance in RNA virus infections emphasizes the requirement for multiple drug targets to limit viral escape.…”
Section: Introductionmentioning
confidence: 99%